0305 Degraded Fractal Activity Regulation Is Associated with Reduced Regional Cortical Gray Matter Volumes - Beyond the Brain Correlates of Sleep Fragmentation. (27th April 2018) - Li, P; Yu, L; Arfanakis, K; Lim, A S; Buchman, A S; Schneider, J A; Bennett, D A; Hu, K
Abstract: Introduction: Human motor activity possesses fractal structures as characterized by similar fluctuation patterns across multiple time scales from seconds to hours. Such fractal regulation (FR) is robust in healthy young subjects and is degraded with aging. Evidence indicates a mechanistic link between fractal regulation and sleep/circadian control. Here, we tested whether FR degradation is associated with changes in brain structure and whether the FR brain correlates overlap with those for sleep disturbance in older adults. Methods: We examined motor activity recordings of 338 older non-demented adults (age: 81.5 ± 7.1 [SD]) in the Rush Memory and Aging Project. All participants underwent magnetic resonance imaging and actigraphy assessment (continuously recorded motor activity for 10 days) in the same year. Gray matter volumes of 34 cortical and 10 subcortical regions were obtained. To assess FR, temporal correlations in activity fluctuations at time scales 0.1–1.5h were examined. We explored the associations between FR and gray matter volumes using bivariate Pearson correlation with Bonferroni correction. We confirmed the associations using linear regression models adjusted for age, sex, and years of education. Results: Fractal activity correlations were positively associated with gray matter volumes in 14 cortical regions and 2 subcortical regions (Bonferroni corrected p <0.05). After adjustment for age, sex, and education, the associations remained in 13 cortical and 1 subcortical regions, including 7 regions that are known to be linked to Alzheimer's disease pathology: lateral orbitofrontal, supra marginal, isthmus cingulate, superior temporal, fusiform, and accumbens area. Conclusion: Using the same database, we previously found that lower gray matter volumes in the lateral orbitofrontal cortex and inferior frontal gyrus pars orbitalis are associated with greater sleep fragmentation. Thus, FR degradation and sleep fragmentation involve certain common brain region in older adults (lateral orbitofrontal cortex), while FR degradation involves the decrease of gray matter volumes in more brain regions. Support (If Any): This work was supported by NIH grants R01AG048108, R00HL102241, P01AG009975, R01AG017917, and R01NS078009.